Spatial distribution of mercury and other potentially toxic elements using epiphytic lichens in Nova Scotia. (February 2020) - Klapstein, Sara J.; Walker, Allison K.; Saunders, Cardy Hallett; Cameron, Robert P.; Murimboh, John D.; O'Driscoll, Nelson J.
Abstract: The use of naturally occurring epiphytic lichens can be an effective tool for regional monitoring of mercury (Hg) and other potentially toxic elements (PTEs). Nova Scotia, Canada is a hotspot for mercury and other trace metal accumulation in ecosystems; partially attributed to long-range transport of air pollution. The relative contribution of local and international sources of Hg to local air in Nova Scotia is unknown. This study assessed the potential of epiphytic lichens ( Usnea spp.) as passive samplers for PTE air pollution in Nova Scotia. Lichens (n = 190) collected across mainland Nova Scotia were analyzed for PTEs. Results indicate that there are 3 distinct clusters of PTEs which suggest patterns and sources for each elemental cluster. Hg was correlated with longitude and prevailing wind direction, and Hg was not significantly different in site-specific hotspot sampling nor year of sampling. Our data support the hypothesis that Hg in lichens is from historical and ongoing long-range transport and diffuse emission patterns rather than localized pollution sources. PTE concentrations were shown to have median values that are similar to other remote regions (such as the Antarctic) however the maximum values were observed to be substantially higher for some elements (e.g. lead, cadmium). This research supports the use of lichens as biomonitors and provides a baseline for future monitoring efforts to identify changes in PTE distribution in Nova Scotia with ongoing industrial activity and a changing climate. Graphical abstract: Image 10804 Highlights: Epiphytic lichens were used as passive samplers for air pollution. Data support the hypothesis that lichen Hg is from historical long-range transport. Potentially toxic elements had concentrations similar to other remote regions. Element clustering indicated both long-range atmospheric and mineral sources. Provides baseline data for identifying changes in trace metal distribution. Abstract : Spatial variability of potentially toxic elements (PTEs) can be monitored using epiphytic lichens to make inferences on source, be it long range transport, nearby pollution, or local mineralogy.